The Antibody Dependant Neurite Outgrowth Modulation Response Involvement in Spinal Cord Injury - Capuz, Alice; Karnoub, Mélodie-Anne; Osien, Sylvain; Rose, Mélanie; Mériaux, Céline; Fournier, Isabelle; Devos, David; Vanden Abeele, Fabien; Rodet, Franck; Cizkova, Dasa; Salzet, Michel (Frontiers in Immunology, 2022)
Spinal Cord Injury (SCI) represents a major medical challenge. At present, there is still no cure to treat it efficiently and enable functional recovery below the injury site. Previously, we demonstrated that inflammation determines the fate of the physiopathology. To decipher the molecular mechanisms involved in this process, we performed a meta-analysis of our spatio-temporal proteomic studies in the time course of SCI. This highlighted the presence of IgG isotypes in both spinal cord explants and their secretomes. These IgGs were detected in the spinal cord even if no SCI occured. However, during the time course following SCI, abundance of IgG1 and IgG2 subclasses (a, b, c) varied according to the spatial repartition. IgG1 was clearly mostly abundant at 12h, and a switch to IgG2a was observed after 24h. This IgG stayed predominant 3, 7, and 10 days after SCI. A protein related to IgM as well as a variable heavy chain were only detected 12h after lesion. Interestingly, treatment with RhoA inhibitor influenced the abundance of the various IgG isotypes and a preferential switch to IgG2c was observed. By data reuse of rat dorsal root ganglion (DRG) neurons RNAseq datasets and RT-PCR experiments performed on cDNA from DRG sensory neurons ND7/23 and N27 dopaminergic neural cell lines, we confirmed expression of immunoglobulin heavy and light chains (constant and variable) encoding genes in neurons. We then identified CD16 and CD32b as their specific receptors in sensory neuron cell line ND7/23 and their activation regulated neurites outgrowth. These results suggest that during SCI, neuronal IgG isotypes are released to modulate neuronal outgrowth. Therefore, we propose a new view of the spinal cord injury response involving an antibody dependent neurite outgrowth modulation (ADNM) which could be a precursor of the neuroinflammatory response in pathological conditions.